Unlocking UMKM Potential: How Employee Satisfaction Mediates HRM Practices to Enhance Employee Performance in the Global Landscape – Case Study of the Kaboki Woven Bag Industry - Lutfi; Mukhlis, Imam; Murwani, F Danardana (PT FORMOSA CENDEKIA GLOBAL, 2024)
This study focuses on unlocking the potential of Micro, Small, and Medium Enterprises (MSMEs) and how employee satisfaction mediates human resource management (HRM) practices to enhance employee performance globally. Through a case study of the KABOKi Woven Bag Industry, this research explores the relationship between employee satisfaction, HRM practices, and employee performance. Involving a population of 112 employees in this industry, a sample of 87 employees was selected using the Slovin technique. Findings highlight the crucial role of employee satisfaction as a mediator between HRM practices and employee performance in facing challenges and opportunities in the global market. The results of this study contribute significantly to stakeholders in developing effective HRM strategies to strengthen MSMEs' employee performance on an international scale